Protecting the Rights of People with Autism in the Fields of Education and Employment: International, European and National Perspectives. - Della Fina, Valentina; Cera, Rachele (Springer Nature, 2015)
European Law; Human Rights; International and Comparative Education; Private International Law, International & Foreign Law, Comparative Law; Law and Psychology.